Occupational Therapy Practitioners’ Perspectives on Occupation-Based Interventions for Clients With Hip Fracture - Wong, Carin (Am J Occup Ther, 2018)
OBJECTIVE. Occupational engagement is the foundation of occupational therapy. We identified perspectives of 18 occupational therapy practitioners on integrating occupation-based interventions during postacute care (PAC) rehabilitation for persons with hip fracture to identify occupational therapy’s distinct contribution. METHOD. We conducted six focus groups derived from a purposive national sample of occupational therapy practitioners (N = 18). A secondary analysis was conducted to analyze the transcripts for major subthemes around occupation-based interventions. RESULTS. Three major themes arose from practitioners’ perspectives regarding the role of occupation in rehabilitation: (1) conducting an occupational profile, (2) integrating occupation-based intervention in the facility, and (3) identifying goals for occupational engagement after discharge. Challenges and strategies for integrating occupation-based interventions were also identified. CONCLUSION. Identifying practitioners’ perspectives on integrating occupation into rehabilitation may inform strategies to facilitate occupation-based interventions in PAC and define occupational therapy’s role in this setting.